Tertullian and the church - Rankin, David (Cambridge University Press, 1995)
Was Tertullian of Carthage a schismatic? How did he view the Church and its bishops? How did he understand the exercise of authority within the Church? In this study David Rankin sets the writings of Tertullian in the context of the early third-century Church and the developments it was undergoing in relation to both its structures and its self-understanding. He then discusses Tertullian's own theology of the Church, his imagery and his perception of Church office and ministry. Tertullian maintained throughout his career a high view of the Church, and this in part constituted the motivation for his vitriolic attacks on the Church's hierarchy after he had joined the New Prophecy movement. His contribution to the development of the Church has often been misunderstood, and this thorough exploration provides a reassessment of its nature and importance.